The Impact of Chronic Discogenic Low Back Pain: Costs and Patients' Burden - Geurts, José W. (Pain Res Manag, 2018)
INTRODUCTION: Chronic discogenic low back pain (CDP) is frequently diagnosed in patients referred to specialized pain clinics for their back pain. The aim of this study is to assess the impact of CDP both on the individual patient and on society. MATERIALS AND METHODS: Using the baseline records of 80 patients in a randomized trial assessing the effectiveness of a new intervention for CDP, healthcare and societal costs related to back pain are calculated. Furthermore, the impact of the condition on perceived pain, disability, health-related quality of life, Quality of life Adjusted Life Years (QALY), and QALY loss is assessed. RESULTS: Using the friction costs approach, we found that the annual costs for society are €7,911.95 per CDP patient, 51% healthcare and 49% societal costs. When using the human capital approach, total costs were €18,940.58, 22% healthcare and 78% societal costs. Healthcare costs were mainly related to pain treatment. Mean pain severity was 6.5 (0–10), and 46% suffered from severe pain (≥7/10). Mean physical limitations rate was 43.7; 13.5% of the patients were very limited to disabled. QALY loss compared to a healthy population was 64%. DISCUSSION: This study shows that in patients with CDP referred to a pain clinic, costs for society are high and the most used healthcare resources are pain therapies. Patients suffer severe pain, are physically limited, and experience a serious loss in quality of life.